(untitled) (Bioagro, 2018)
This experiment was conducted during four consecutive years (2012-2016) at a field in Zamora District, Aragua State, Venezuela, to evaluate the effect of cow manure (CM) on DK-357 corn growth and yield and some chemical properties of soil. The experimental design was a randomized complete block, with four replications. Plots were 5.0 x 6.0 m2, containing five rows of 6 m length, spaced 1.0 m apart and 0.25 m between plants. Cow manure rates applied were 60, 120 y 180 Mg ha-1. Additionally, a chemical control CC (120 kg∙ha-1 of N as urea) and an absolute control (neither CM nor CC) were used. The whole experimental site received 60 kg∙ha-1 P2O5 and 60 kg∙ha-1 K2O at sowing. Same rates were applied each crop cycle each year, at same plots planted with the crop. Three samplings were performed, both plant and soil, 30, 60 and 120 days after planting. Soil samplings were executed at 15, 30 and 45 cm deep. Continuous application of cow manure had a positive effect on plant height, stem diameter, leaf area index, nitrate in sap, dry matter and grain yield. Contents of organic matter and soil nitrate were higher at 0-15 cm deep, at higher cow manure rates, in all samples. Electrical conductivity values increased in function of cow manure rates, without salt stress symptoms in the corn crop.